P‐62: Effect of Viewpoints of Integral Image 3D display on Human Eye Accommodation Response. Issue 1 (25th September 2020) - Chen, Cong; Deng, Huan; Wang, Qiong-Hua; Zhong, Fei-Yan; Ji, Qing-Lin; Li, Qiang
Abstract : To obtain the effect of the viewpoint number on the accommodation response of human eyes, we measure the accommodation response of the human eyes when we view the 3D images with 8×8, 6×6, 4×4, 2×2, 1×1 viewpoints, and compare the results with the accommodation response when viewing real target.